PENGARUH TAMPILAN DAN CITA RASA PRODUK PADA MENU BEST SELLER TERHADAP KEPUASAN PELANGGAN DI CAFE LUAR GARIS TIBAN KOTA BATAM - Sipayung, Natal Olotua; Julia Putri, Nadila Aurora; Dailami, Dailami (JURNAL MENATA, 2024)
The aim of the research is to determine the effect of the appearance and taste of products from the best seller menu on customer satisfaction at the Luar Garis Cafe Tiban, Batam City, in this case the best seller menu used is the typical Luar Garis Fried Rice. The research method used was a quantitative approach and descriptive analysis method. By using multiple linear analysis, namely partial influence test and simultaneous influence test. The results of the research show that the significant value for the appearance and taste of the product is 0.00 which is smaller than 0.05 in the partial influence test and in the simultaneous influence test the appearance and taste of the product shows a fcount value of 85.158 which is greater than f table 3.09 so that the appearance and taste of the product have an influence simultaneously. There is also a coefficient of determination test which shows that 63% of the product appearance and taste variables simultaneously influence the customer satisfaction variable. The conclusion of this research is that the appearance and taste of the product have a significant influence on customer satisfaction.